Customer relationship management and the social and semantic web : enabling cliens conexus - Colomo-Palacios, Ricardo, 1973-; Varajao, Joao, 1972-; Soto-Acosta, Pedro, 1979- (Hershey, PA : Business Science Reference, 2012)
'This book provides an overview of the field of the Semantic Web, social Web and CRM by uniting various research studies from different subfields, exploring the opportunities and challenges confronting organizations using Web 2.0 and 3.0'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Customer relations -- Management; Semantic Web; Online social networks